Le scelte di politica economica fra teoria ed evidenze empiriche: un approccio storicistico - Capuano, Giuseppe (Argomenti, 2015)
The principal objective of the article is to show how the economic theory is not an exact science. It does no't have universal value and it is not just link to mathematics, because it does not make itself as a scientific discipline. For this economics has not to use too much mathematics to imitate the exact sciences, The approach that we would like to propose in this article is a “historicist” vision of the economic theories. It wants to be more pragmaticas and less dogmatic to  the advantage to deliver unassailable theories from economists, but simply ideas with solid scientific bases and supported by some statistic bases. It represents exactly what a policy maker needs to make decision in a right historical moment.